Language learning and teaching in a multilingual world - Narcy-Combes, Marie-Françoise; Narcy-Combes, Jean-Paul, 1947-; McAllister, Julie, 1966-; Leclère, Malory; Miras, Grégory (Bristol ; Blue Ridge Summit : Multilingual Matters, 2019)
The majority of people around the world live in multilingual societies, and so it follows that plurilingualism should be considered normal. This book proposes a flexible and adaptive framework for designing and implementing language learning environments and tasks, which will be useful for practitioners working in classrooms where many languages are already spoken. The authors begin by presenting a state-of-the-art review of current research on language learning, language teaching and multilingual language acquisition. This is followed by a qualitative review of 37 multilingual research projects, which are treated as case studies to inform the practical guidance that constitutes the remainder of the book. The information and practical framework contained within this book will be of interest to both researchers, teachers and teacher educators.
Frontmatter -- Contents -- Introduction -- Epistemological Stance -- Some Important Definitions -- Context -- Chapter Organisation -- Part 1: Reference Theories: Interrelationships and Complementarities -- Part 2: Multilingual Practices in Action -- Part 3: Designing Contextualised Language Learning Environments in a Plurilingual Perspective -- References -- Index
Includes bibliographical references and index.
Description based on online resource; title from digital title page (viewed on August 28, 2019).
JSTOR
Keywords: Language and languages -- Study and teaching; Multilingualism; Langage et langues -- Étude et enseignement; Multilinguisme; Bilingualism & multilingualism; Language acquisition; FOREIGN LANGUAGE STUDY -- Multi-Language Phrasebooks; LANGUAGE ARTS & DISCIPLINES -- Alphabets & Writing Systems; LANGUAGE ARTS & DISCIPLINES -- Grammar & Punctuation; LANGUAGE ARTS & DISCIPLINES -- Linguistics -- General; LANGUAGE ARTS & DISCIPLINES -- Readers; LANGUAGE ARTS & DISCIPLINES -- Spelling; LANGUAGE ARTS & DISCIPLINES / Study & Teaching; Language and languages -- Study and teaching; Multilingualism; Language learning Environments .; Multilingual learners; Multilingualism .; Plurilingualism; TBLT; Task-based language teaching; language education; traditional language learning classrooms .